How Much Is Enough? Explaining the Continuous Transparency Conflict in TTIP - Gheyle, Niels (2017)
Transparency has been a central issue in the debate regarding the Transatlantic Trade and Investment Partnership (TTIP), especially on the side of the European Union (EU). The lack of transparency in the negotiating process has been one of the main criticisms of civil society organizations (CSOs). The European Commission (EC) has tried to gain support for the negotiations through various ‘transparency initiatives’. Nonetheless, criticism by CSOs with regard to TTIP in general and the lack of transparency in specific remained prevalent. In this article, we explain this gap between various transparency initiatives implemented by the EC in TTIP and the expectations on the side of European CSOs. We perform a content analysis of position papers on transparency produced by CSOs, mainly in response to a European Ombudsman consultation, complemented by a number of official documents and targeted interviews. We find that the gap between the TTIP transparency initiatives and the expectations of CSOs can be explained by different views on what constitutes legitimate trade governance, and the role of transparency, participation, and accountability herein.